Implementation of Leech Therapy to Reduce Pain in Patients with Circulatory Problems at Griya Sehat Muslimah Srengseng Kembangan, West Jakarta - Alfian; Yuniawati (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2024)
Circulatory disorders are a health problem that often causes chronic pain and reduces quality of life. Leech therapy is a traditional method that has the potential to improve circulation and reduce pain through the natural anticoagulant effect of leech saliva. This study aims to evaluate the effectiveness of leech therapy in reducing pain in patients with circulatory disorders at Griya Sehat Muslimah Srengseng Kembangan, West Jakarta. This study was a quasi-experimental study with a pre-test and post-test approach in 12 patients with circulatory disorders. Each patient underwent leech therapy three times over two weeks. Pain intensity was measured before and after therapy using a Visual Analog Scale (VAS). The results showed a significant decrease in pain intensity after therapy. The average reduction in pain on the VAS scale was 3.7 points after three treatments, indicating that leech therapy is effective in reducing pain in patients with circulatory disorders. Leech therapy has been proven effective in reducing pain in patients with circulatory disorders. This therapy can be a non-pharmacological alternative for managing pain in patients with circulatory disorders